2017
DOI: 10.2147/ott.s141538
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab combined with concurrent chemoradiotherapy benefits patients with advanced nasopharyngeal carcinoma

Abstract: BackgroundThe potential benefits and possible risks associated with combined nimotuzumab and concurrent chemoradiotherapy in patients with advanced nasopharyngeal carcinoma (NPC) have yet to be determined.MethodsThe databases PubMed, Web of Science, China National Knowledge Infrastructure, and Wanfang were systematically searched through February 2017 for studies comparing combined nimotuzumab and chemoradiotherapy versus chemoradiotherapy alone in the treatment of NPC. Primary outcomes were complete and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…Therefore, Nimo concurrent with IC followed by CCRT might be the optimal mode of sequential treatment for patients with advanced NPC. The results in our study were quite different from the current thinking in the field, which could be because all the published data are based on the application of Nimo with CCRT [25][26][27]. To the best of our knowledge, there are few studies reporting that Nimo can be applied concurrently with IC to treat NPC.…”
Section: Dcontrasting
confidence: 95%
“…Therefore, Nimo concurrent with IC followed by CCRT might be the optimal mode of sequential treatment for patients with advanced NPC. The results in our study were quite different from the current thinking in the field, which could be because all the published data are based on the application of Nimo with CCRT [25][26][27]. To the best of our knowledge, there are few studies reporting that Nimo can be applied concurrently with IC to treat NPC.…”
Section: Dcontrasting
confidence: 95%
“…In a phase II study of nimotuzumab plus RT for stage III to IVb NPC, the nimotuzumab add-on group was superior to the placebo add-on group, resulting in a significantly higher complete remission rate (90.63% vs. 51.52%, respectively, P = .02) and higher 3-year overall survival rate (84.29% vs. 77.61%, respectively, P < .05) without increasing radiation-related adverse events [37] . Our phase II study has shown that compared with chemoradiotherapy (CRT), nimotuzumab plus CRT produced the similar efficacy without increasing the acute severe dermatitis/mucositis for LA NPC [38] . Similar results were also observed in some retrospective study where nimotuzumab was combined with concurrent CRT in treatment LA NPC [27] , [28] .…”
Section: Discussionmentioning
confidence: 94%
“…Firstly, NPC has distinct biological characteristics from other solid tumors, so that the prognostic factors may be different; Secondly, chemoradiotherapy is the standard treatment modality for locoregionally advanced NPC currently, whereas patients in this retrospective study received combined nimotuzumab with chemoradiotherapy, so that the treatment outcomes may be changed with the addition of nimotuzumab. Several previous studies concluded that nimotuzumab combined with chemoradiotherapy benefited patients, and was more effective than chemoradiotherapy alone [10][11][12].…”
Section: Subclinical Hypercoagulation Condition Is Common In Cancer Pmentioning
confidence: 99%
“…Thus, nimotuzumab is recommended as an adjunct to radiotherapy for locoregionally advanced NPC. Subsequently, several retrospective researches confirmed that combining nimotuzumab with chemoradiotherapy increased treatment efficacy and improved prognosis with tolerable toxicities [10][11][12]. However, it is important to note that not all patients benefit from the concurrent treatment of nimotuzumab.…”
Section: Introductionmentioning
confidence: 99%